Takotsubo cardiomyopathy - Webb Webb, Kembly María (2019)
Takotsubo cardiomyopathy is a recently described entity (in 1990 in Japan). This pathology occurs mainly in postmenopausal women, and the greater incidence has been described during the summer. The pathophysiology of the disease is not completely clear at present; however, the catecholaminergic excess, triggered by physical or emotional stress and the subsequent inhibition of adrenergic receptors may be responsible. Takotsubo cardiomyopathy presents clinically indistinguishable from infarction, and is necessary the laboratory tests and imaging studies to perform the differential diagnosis. This disease present a good prognosis, but complications can occur